Meloidogyne incognita-Induced Giant Cells in Tomato and the Impact of Acetic Acid - Christianna Meidani; Konstantinos Telioglanidis; Eleni Giannoutsou; Nikoleta Ntalli; Ioannis Dimosthenis S. Adamakis (Plants)
The plant parasitic root-knot nematodes of the species Meloidogyne incognita infect many cultivated plants, one of which is the tomato (Solanum lycopersicum). To be fed, M. incognita selects unique feeding sites inside the root and induces the formation of large galls (knots) encompassing the so-called giant cells (GCs). In the present study, a comparative analysis of the GCs/root cell and cell wall components between M. incognita-infected and uninfected tomato plants and plants pre-treated with the plant biostimulant and nematicide acetic acid (AA) was carried out. Pectin, hemicellulose and extensin epitopes were detected in tomato root sections. M. incognita-induced GCs in tomato roots had cell walls with arabinans, unesterified/methylesterified homogalacturonans and xyloglucans, but were devoid of mannans and extensins. Interestingly, the above epitope distribution also differed in root sections made near the formed root knot, proximal to the root cap. Moreover, it seemed that AA was able to induce the deposition of extensins in AA-treated, M. incognita-uninfected roots and hamper the GC development in AA-treated, M. incognita-infected roots. According to the above the AA, stimulates natural defense mechanisms in tomato, thus protecting it from nematode infestation.